Review on the application of acupoint sticking therapy for constipation in adult patients (中医穴位贴敷疗法在成人便秘中的应用研究进展) - WANG Xiaomin (王晓敏); ZHENG Naihua (郑乃花); YANG Dongmei (杨冬梅); E Haiyan (鄂海燕); ZHANG Lijun (张丽君); LIU Xiaoliu (刘晓柳) (中西医结合护理)
Constipation is a common digestive system disease caused by bad living habits or gastrointestinal dysfunction. The purpose of this paper is to summarize the risk factors, epidemiological investigation, Traditional Chinese Medicine cognition and treatment principles of constipation in adult patients, and analyze the research status of Traditional Chinese Medicine acupoint application therapy for constipation in adult patients, in order to provide a reference for the clinical practice and further exploration of appropriate techniques of Traditional Chinese Medicine. (便秘是由于不良的生活习惯影响, 或者胃肠道功能紊乱造成的生活中常见的一种消化系统疾病。本文旨在通过对成人便秘患者的危险因素、流行病学调查、中医认知及治疗方案等进行总结归纳, 以期为中药穴位贴敷疗法应用于成人便秘患者的临床护理提供参考, 为中医适宜技术应用于便秘患者的探索提供可循依据。)